Parvovirus B19 Myocarditis: Looking Beyond the Heart. (April 2020) - Izquierdo-Blasco, Jaume; Salcedo Allende, María Teresa; Codina Grau, Maria Gemma; Gran, Ferran; Martínez Sáez, Elena; Balcells, Joan
Human parvovirus B19 represents the most common etiology of myocarditis in the pediatric population. Although it usually causes a benign exanthematic viral infection, parvovirus B19 may also present as disseminated disease with tropism for the myocardium, causing heart failure with high mortality. We present the case of a 2-year-old patient with fulminating acute myocarditis in whom the histological, immunophenotypic, and microbiological findings in necropsy showed multiorgan involvement caused by parvovirus B19. The autopsy revealed changes due to infection with parvovirus B19 as well as hypoxic-ischemic and secondary autoimmune changes. Medullary aplasia was observed, transmural lymphocyte myocarditis, lymphocytosis in the dermis with endothelial cells positive for parvovirus B19 in immunohistochemistry, cholestatic hepatitis due to ischemia and autoimmune hepatitis, lymphadenitis, and signs of hemophagocytosis. We also found hypoxic-ischemic encephalopathy.